2017
DOI: 10.1186/s12886-017-0568-2
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond laser-assisted cataract surgery in patients with phakic intraocular lenses and low endothelial cell counts: a case report

Abstract: BackgroundPhakic intraocular lens (PIOL) implantation has been used to correct myopia and myopic astigmatism, although corneal decompensation can occur after implantation. Femtosecond laser-assisted cataract surgery (FLACS) has gained in popularity due to its lower postoperative astigmatism and endothelial loss. Herein, we report the use of FLACS in patients who previously received PIOL implantation and have a low corneal endothelial cell count.Case presentationTwo patients with a previous iris-claw PIOL impla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…Several authors have described the use of FLACS in eyes with anterior and posterior chamber ICLs. [345678] Anisimova et al reported bubbles similar to ours which lead to incomplete capsulotomy but did not interfere with nuclear fragmentation. [4] Similarly, Kaur et al reported incomplete nucleotomy due to bubble entrapment.…”
Section: Discussionsupporting
confidence: 76%
“…Several authors have described the use of FLACS in eyes with anterior and posterior chamber ICLs. [345678] Anisimova et al reported bubbles similar to ours which lead to incomplete capsulotomy but did not interfere with nuclear fragmentation. [4] Similarly, Kaur et al reported incomplete nucleotomy due to bubble entrapment.…”
Section: Discussionsupporting
confidence: 76%
“…91 More recently, indicating its surgical potential, the FL has been used to transect IOLs which require exchange 92 and can be used without adverse effect in cataract surgery with coexisting phakic IOLs and low endothelial counts before phakic IOL removal. 93 The FL can also be used to perform a primary laser posterior capsulotomy just prior to or just after IOL insertion 94,95 and has been used to this effect in paediatric congenital cataract cases. 96…”
Section: Use Of Flacs In Complicated Cataract Surgerymentioning
confidence: 99%
“…In our patient, the level of ECD was only about 60 to 70% that of ordinary healthy individuals in the Chinese population [ 24 ]. Although the ECD was not very low compared to that of those undergoing phacoemulsification in previous reports [ 10 , 26 ], there was still a chance to develop corneal decompensation after the intraocular procedure. As a result, topical AA was still applied to our patient for one month postoperatively to ensure the normal level of ECD.…”
Section: Discussionmentioning
confidence: 73%